Experimental Investigation on Shear Strength between Ultra-High-Performance Concrete and Normal Concrete Substrates - Xinghong Jiang; Hengxiang Song; Ke Li; Jing Qiang; Jing Tian (Advances in Materials Science and Engineering, 2023)
Tunnel engineering in China has developed to the stage of both construction and maintenance, and the problem of structural defect is widespread. The cast-in-situ jacketed arch treatment takes a long time and has a great impact on traffic. It is urgent to develop prefabricated treatment technology, and the guarantee of mechanical properties of the prefabricated UHPC-post-cast NC interface is the key problem. Through the oblique shear test, combined with the XTDIC full-field strain monitoring system, the failure process and failure mode of UHPC-NC specimens were studied and analyzed under different interface keyway numbers (0, 1, 2, and 3), interface agents (meshless interface agent, cement slurry, silica fume modified cement slurry, modified cement slurry mesh, cement slurry, and expansion agent), and NC pouring grades (C30, C35, C40, and C50), as well as the influencing factors of shear strength, shear stiffness, and the slip model of the bonding interface. The results show that there are four typical failure modes in UHPC-NC under compression and shear, including complete interface failure (Class A), interface failure + NC shear failure (Class B), NC compression failure (Class C), and interface failure + NC compression failure + NC slip failure in the keyway (Class D). The complete interface failure type (Type A) without keyway treatment has sudden failure, and the keyway has the ability to disperse load and limit interface slip. The principal strain decreases along the normal sides of the interface, and the influence range of UHPC and NC sides is about 16.2 mm and 17.5 mm, respectively. In practice, the thinnest part of the treatment structure should not be less than 2 cm. The shear strength of the prefabricated UHPC-post-pouring NC interface is generally low, and the maximum shear strength of 13.9 MPa obtained by the test is still lower than the recommended value of 14–21 MPa of ACI 546.3R-14. In treatment design, the interface shear reinforcement can be introduced to ensure the cooperative bearing capacity. The shear strength of the prefabricated UHPC-post-poured NC interface is slightly affected by the interface agent and postpoured concrete grade and increases linearly with the increase in the number of keyways. When the number of keyways is equivalent to the roughness index, the relationship between the shear strength and the roughness is as follows: fs=1.664+3.030Rz. Under the action of keyway, the interface slip of UHPC-NC can be simplified into four stages: the interface slip stage, the keyway strengthening stage, the shear yield stage, and the specimen failure stage. Based on this, a prefabricated UHPC-post-pouring NC interface slip model was proposed, and the experimental results of key parameters such as interface bond strength, stiffness, and slip amount at different stages were obtained by fitting. In the keyway strengthening stage, the shear stiffness increases linearly first and then tends to be stable with the increase in the number of keyways. The maximum shear stiffness is about 20 MPa/mm, and the maximum interfacial slip increases with the increase in the number of keyways, which improves the overall shear resistance. The results can be used in the design of a tunnel-fabricated treatment segment.